Związek zaburzeń glacitektonicznych z pradolinami na terenie Polski zachodniej = Relation between glaciotectonic deformations and ice marginal valleys in west Poland - Kraiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents an analysis concerning a relation between glaciotectonic deformations and glaciotectonic depressions. The research work lead to the conclusion that (it is a rule) the fargest (the longest and the broadest) zones of glaciotectonic deformations occur in the area south of ice marginal valley.
Keywords: zaburzenia glacitektoniczne; depresja glacitektoniczna; elewacja glacitektoniczna; glaciotectonic deformations; glaciotectonic depression and elevation